Grazing capacity of reindeer pastures in the boreal zone of the West Siberian Plain - Korkina Elena; Kushanova Aliya; Seredovskich Boris (BIO Web of Conferences, 2023)
Field studies were carried the grazing capacity of the reindeer in the boreal zone. The study is based on the study phytomass forage plants of the reindeer grazing. Soil, geobotanical descriptions were made grazing capacity on the methodology for determining productivity and calculating the fodder capacity of reindeer pastures. The identification of potentially suitable places for the reindeer was carried out on the basis of the decryption of satellite images and the digitization of thematic maps. Grazing capacity was with the allocation on the geobotanical map of the areas of distribution of pine-lichen white-moss and pine lichen-cowberry forests, and on the soil map - the areas of finding illuvial-ferruginous podzols. The study revealed that best the landscape-ecological conditions for the growth of lichens of the species Cladonia alpestris (L.) are the pinery on the podzols in Siberian ridges (Siberian Uvals). Based on the results of field studies, the fodder capacity of reindeer pastures for the studied areas was calculated, and the estimated number of deer was determined. The conducted studies make it possible to judge the state of individual areas suitable for reindeer habitats, and thus make it possible to assess the degree of prospects for reindeer breeding.